2019
DOI: 10.1161/hypertensionaha.119.13287
|View full text |Cite
|
Sign up to set email alerts
|

ANO4 (Anoctamin 4) Is a Novel Marker of Zona Glomerulosa That Regulates Stimulated Aldosterone Secretion

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Based on our investigation, we suggest that these associations result mainly from reduced or loss of ANO4 activity in the affected tissues. The recently reported role of ANO4 in the regulation of aldosterone secretion fits into the observation that ANO4 is preferentially expressed in tissue with secretory activity [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Based on our investigation, we suggest that these associations result mainly from reduced or loss of ANO4 activity in the affected tissues. The recently reported role of ANO4 in the regulation of aldosterone secretion fits into the observation that ANO4 is preferentially expressed in tissue with secretory activity [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 55%
“…Additionally, recently, literature reported a link between ANO4 expression and some disease mechanisms. The group of Brown and colleagues suggested that ANO4 might be involved in the regulation of aldosterone secretion [ 18 , 19 ]. Furthermore, active myelin-lesions in multiple sclerosis display increased levels of ANO4 expression [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Potassium Two Pore Domain Channel Subfamily K Member 5 ( KCNK5 or TASK2 ) channel is also consistently less expressed in APAs compared to normal adrenal cortex [ 65 ]. Recently, Anoctamin 4 ( ANO4 ), a calcium dependent chloride channel, was found to be significantly downregulated in APAs compared to normal ZG, independent of their respective mutation status [ 66 ]. Expression data on L-type and T-type voltage dependent calcium channels has demonstrated high CACNA1H expression in both normal adrenal glands and APAs, while CACNA1A, CACNA1C and CACNA1E expression was significantly upregulated in APAs [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the herein reported GRK2-dependent βAR-AT 1 R crosstalk in AZG cells might not take place at the level of the receptors per se and the signaling of the two receptors could converge at some receptor-proximal downstream effector modulated by GRK2 instead. For instance, the calcium-regulated chloride channel TMEM16A (anoctamine-1), which is activated by calcium/calmodulin-dependent kinase phosphorylation, was very recently implicated in the stimulation of aldosterone production in AZG cells [30,31]. βAR-activated GRK2 may very well phosphorylate and activate this channel, thereby mediating the stimulation of aldosterone secretion by both βARs and AT 1 Rs (AT 1 R elicits intracellular [Ca 2+ ] elevation via G q/11 proteins [23], and Ca 2+ activates TMEM16A).…”
Section: Discussionmentioning
confidence: 99%